Hypertension attenuates COVID-19 vaccine protection in elderly patients: a retrospective cohort study - Yuan, Zhen; Wong, Iong Fong; Xu, Ren-He; Zhang, Xiao Zhan; Lei, Chon Lok (Frontiers in Immunology, 2025)
The COVID-19 pandemic has severely impacted elderly populations, particularly those with comorbidities. This study evaluated the effects of COVID-19 vaccination on 193 hospitalized elderly patients (≥ 60 years) in Macao. Vaccination was suggestively associated with a 2.3-fold higher likelihood of prognostic improvement (adjusted OR = 2.3, 95% CI: 0.980-5.940, P = 0.065), while hypertension significantly reduced the improvement rate by 67.5% (P = 0.039). Vaccinated patients also exhibited lower Modified Early Warning Scores and reduced mortality. These findings underscore the protective role of vaccination in improving prognosis among high-risk elderly patients and highlight the need for tailored strategies for those with comorbidities.